Optimization of IT-Based Remedial Test to Improve the Economic Ability of OSN-K Students at SMAN 1 Sumberpucung - Adrian Hartanto Darma Sanputra; Tatas Ridho Nugroho; Eliza Silviana Miftakh; Shynta Nuril Rahmawati Ahyar; Venni Ayunda Pratiwi (Dinasti Publisher, 2024)
his article discusses efforts to improve the understanding and competence of SMAN 1 Sumberpucung students who will take part in the National Science Olympiad (OSN) at the district level in the field of economics. SMAN 1 Sumberpucung is a school with